Susceptibility to Fluconazole and Voriconazole in Candida Strains Isolated from Blood Culture by Disk Diffusion Method. Maracaibo, Venezuela - Armindo Perozo; Belinda Calvo; Luzmila Mesa; Maritza Pineda (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2011)
To determine the susceptibility of Candida strains isolated from blood cultures in Maracaibo, Venezuela, 78 strains obtained from hospitalized patients in different services of the autonomous Maracaibo University Hospital, Venezuela, were studied. Chromogenic Medium Brilliance Candida Agar and Vitek-YBC were used for species identification. In addition, cultures were assessed using the traditional identification method. Susceptibility was determined by the diffusion method with fluconazole and voriconazole disks, according to the Clinical and Laboratory Standard Institute, Document M44-A2. Frequency of the Candida species was: C. parapsilosis 51.28%, C. tropicalis 15.38%, C. guilliermondii 11.54%, C. albicans 10.26% C. famata 6.41%, C. glabrata 3.85% and C. krusei 1.28%. Susceptibility was 96.15% and 100% for fluconazole and voriconazole, respectively. Three isolates identified as C. albicans, C. guilliermondii and C. krusei were resistant to fluconazole. These results suggest that fluconazole and voriconazole can be useful in the treatment of patients with candidemia; however, epidemiological surveillance and susceptibility pattern determination of Candida must be maintained.